The effects of psychotherapy for depression on anxiety symptoms: a meta-analysis. Issue 13 (24th January 2018) - Weitz, Erica; Kleiboer, Annet; van Straten, Annemieke; Cuijpers, Pim
Abstract : Background: More than half of patients who present with depressive disorders also have elevated comorbid anxiety symptoms. Given the high comorbidity between these disorders, it is important to understand the extent that psychotherapies for depression additionally ameliorate symptoms of anxiety. Methods: Systematic searches were conducted in PubMed, PSYCinfo, EMBASE, and the Cochrane Registry of Controlled Trials. Included studies were randomized controlled trials that compared psychotherapy compared with a control condition for the treatment of adults with a primary diagnosis or elevated symptoms of depression and that examined the effects of treatment on anxiety outcomes. Acute phase depression and anxiety (continuous measure) outcomes were extracted. Effect sizes were calculated by subtracting the average post-treatment scores of the psychotherapy group from the average post-treatment scores of the comparison group divided by the pooled standard deviation. Results: Fifty-two studies of varying quality met the inclusion criteria. Pooled effect sizes showed that anxiety outcomes were significantly lower in the psychotherapy conditions than in control conditions at post-treatment [ g = 0.52; 95% confidence interval (CI) 0.44–0.60; NNT (numbers-needed-to-treat) = 3.50]. Moderate heterogeneity was observed ( I 2 = 55%, 95% CI 40–66). Bivariate metaregression analysis revealed a significant association between depression and anxiety effect sizes at post-treatment Longer-term follow-ups of up to 14 months post-baseline showed indications for a small lasting effect of psychotherapy on anxiety outcomes ( g = 0.27). Conclusions: This meta-analysis provides evidence that psychotherapy aimed at depression can also reduce anxiety symptoms in relation to control conditions.